Taxes and Supply of Labor by Entrepreneurs - Paul, Sanjay; Bechtold, Ademar (Advances in Social Sciences Research Journal, 2015)
We develop a model of entrepreneurship in which an individual allocates time between salaried work (which pays a certain income) and entrepreneurial activity (which yields an uncertain income). The individual pays taxes on both incomes; however we allow for deductibility of interest. We derive the effects of changing tax rates on the supply of labor to the salaried job market and the supply of labor to the entrepreneurial activity. We also investigate the effects of differential sectoral productivity and differing income tax rates on entrepreneurship.